Measuring potassium level in packed red blood cells before using: Word of caution for congenital cardiac surgery. Issue 3 (24th November 2021) - Altun, Dilek; Arnaz, Ahmet; Doğan, Abdullah; Yalçınbaş, Yusuf; Türköz, Rıza; Yüksek, Adnan; Altun, Demet; Abdullah, Taner; Ustalar Özgen, Serpil; Toraman, Fevzi; Sarıoğlu, Tayyar
Abstract: Background and Aim of the Study: Transfusion‐associated hyperpotassemia is a serious complication of packed red blood cell (PRBC) transfusion after congenital cardiac surgery. Our study aimed to identify risk factors and potential preventive measures of transfusion‐associated hyperpotassemia in neonates and infants after congenital cardiac surgery. Methods: Pediatric patients who underwent congenital cardiac surgery and need transfusion were enrolled in this prospective study. The potassium concentration of PRBC was checked from the sample taken from the segment. The volume of transfusion, age of PRBC, potassium concentration of unit were recorded. The estimated increment of potassium level in patients after PRBC transfusion was calculated. Results: Seventy‐four individual patients, 95 distinct transfusions, 112 blood products were evaluated. The mean age of the blood unit was 3.8 ± 1.4 days. The mean potassium concentration in the PRBCs was 9.9 ± 2.4 mmol/L. A weak correlation was observed between the potassium value of the PRBC and the age of PRBC ( p = 0.049, r = 0.2, y = 0.24 × x + −0.68). There was a weak correlation between the potassium value of PRBCs and the age of the unit ( p < 0.001, r = 0.37, y = 2.8 × x + −3.6). Conclusions: Before transfusion, even PRBC is fresh, measuring the potassium level of PRBC and the potassium that will be given to the pediatric patient with transfusion can prevent transfusion‐related hyperpotassemia and related complications. Otherwise, high potassium levels, which may be overlooked despite being fresh, may cause serious complications, even cardiac arrest, especially in neonates and infants.